Exposure to Roundup increases movement speed and decreases body mass in earthworms - Pochron, Sharon T; Mezic, Mateo; Byrne, Samantha; Sasoun, Samy; Casamassima, Alex; Kilic, Melisa; Nuzzo, Amanda; Beaudet, Charles-Edouard (Frontiers in Environmental Science, 2022)
Glyphosate, the herbicidal ingredient in Roundup® products, can persist in soil for months or years, allowing soil invertebrates ample time to encounter and respond to contamination. While Roundup products can negatively impact earthworm (Eisenia fetida) health, they may also provide a direct or indirect food source. In a set of three experiments, we aimed to determine if Roundup® Ready-to-Use III provides a nutritional benefit, damages earthworm health, or both. We used cameras and ant-farm-style habitats to measure how exposure to a commonly used Roundup formulation impacted earthworm foraging speed as measured by the amount of soil displaced per minute. We also assessed whether contamination drove changes in earthworm body mass and stress test survival time. We found that worms living in contaminated soil decreased body mass and displaced more soil per minute relative to earthworms living in non-contaminated soil, suggesting that contamination offered no nutritional benefit. Exposure to contamination did not significantly impact earthworm survival time during a stress test, suggesting weak direct toxicity. Exposure to this contaminant drove a decrease in body mass and increase in movement, which outside of the lab might increase the speed of tunnel formation and microbial dispersal, at a cost to the earthworms. The results of these experiments highlight the need to understand the relationship between Roundup formulations, earthworm behavior and health, and the interplay between earthworm behavior and soil health.